Developmentally Regulated Oscillations in the Expression of UV Repair Genes in a Soilborne Plant Pathogen Dictate UV Repair Efficiency and Survival - Shira Milo-Cochavi (American Society for Microbiology, 2019)
ABSTRACT The ability to withstand UV damage shapes the ecology of microbes. While mechanisms of UV tolerance were extensively investigated in microorganisms regularly exposed to the sun, far less is known about UV repair of soilborne microorganisms. Fusarium oxysporum is a soilborne fungal plant pathogen that is resistant to UV light. We hypothesized that its UV repair capacity is induced to deal with irregular sun exposure. Unlike the SOS paradigm, our analysis revealed only sporadic increases and even decreases in UV repair gene expression following UVC irradiation or exposure to visible light. Strikingly, a major factor determining the expression of UV repair genes was the developmental status of the fungus. At the early stages of germination, the expression of photolyase increased while the expression of UV endonuclease decreased, and then the trend was reversed. These gene expression oscillations were dependent on cell cycle progression. Consequently, the contribution of photoreactivation to UV repair and survival was stronger at the beginning of germination than later when a filament was established. F. oxysporum germinates following cues from the host. Early on in germination, it is most vulnerable to UV; when the filament is established, the pathogen is protected from the sun because it is already within the host tissue. IMPORTANCE Fusarium oxysporum infects plants through the roots and therefore is not exposed to the sun regularly. However, the ability to survive sun exposure expands the distribution of the population. UV from the sun is toxic and mutagenic, and to survive sun exposure, fungi encode several DNA repair mechanisms. We found that Fusarium oxysporum has a gene expression program that activates photolyase at the first hours of germination when the pathogen is not established in the plant tissue. Later on, the expression of photolyase decreases, and the expression of a light-independent UV repair mechanism increases. We suggest a novel point of view to a very fundamental question of how soilborne microorganisms defend themselves against sudden UV exposure.